Вплив введення низьких доз хлорпірифосу до та під час вагітності на постнатальний розвиток другого покоління щурів - Грабовська, Софія; Grabovska, Sofiay (Східноєвропейський Національний університет імені Лесі Українки, 2015)
Досліджено вплив хронічного введення самицям щурів низьких доз хлорпірифосу до запліднення, а також одноразового введення його субтоксичної дози під час вагітності на виживання та параметри раннього постнатального розвитку потомства (темп набору маси, індекс Кетле). У потомстві самиць, інтоксикованих хлорпірифосом, спостерігалася нижча частка виживання, а також статистично достовірні відмінності за обома індексами маси тіла. Chlorpyrifos is an organophosphate pesticide. The main mechanism of its toxicity is acetylcholinesterase inhibition, causing neurological disorders, but it may also affect other body systems. Recently, the effects of pesticide exposure to mothers on deviations in their offspring development are studied actively. In this study, we investigated the effects of chronic chlorpyrifos intoxication of females before fertilization and a single injection of sub-toxic dose of the pesticide at the first trimester of pregnancy on the survival rate of the offspring and parameters of its development at the first 30 postnatal days (weight gain rate, Quetelet body mass index). According to the results, exposure to the highest of presented doses (15 mg / kg daily for 30 days, 4 months prior to pregnancy) caused a statistically significant (compared to control) pups survival decrease, and also a decrease in their body mass indexes, along with a high growth rate. In the other experimental groups, there were similar but less prominent tendencies.
Low Dose Chlorpyrifos Exposure Before and During Pregnancy Alters the Postnatal Development of Rat Offspring.
Keywords: хлорпірифос; щурі; друге покоління; виживання потомства; індекс Кетле; chlorpyrifos; rats; second generation; offspring survival; Quetelet index